Plant Accessible Water Storage Capacity and Tree-Scale Root Interactions Determine How Forest Density Reductions Alter Forest Water Use and Productivity - Tague, Christina L.; Moritz, Max A. (Frontiers in Forests and Global Change, 2019)
Forest disturbances such as wildfire and drought-related disease often lead to declines in productivity that both influence and are influenced by forest water use, particularly in the semi-arid environments of the Western US. Fuel treatments are frequently proposed to reduce vulnerability to these drought-related impacts and in some cases as an approach to increase water yield. By changing ecosystem structure, fuel treatments alter ecosystem function (including hydrologic cycling, carbon sequestration, energy partitioning and biogeochemical cycling). Empirical studies of the impacts of changing ecosystem structure, either through active forest management or through natural disturbances, show a wide range of responses that include both increases and decreases in forest water use. Variation in climate and species, as well as the magnitude of forest density reduction, are commonly proposed as explanations for this variation. In this paper we use a coupled eco-hydrologic model to demonstrate that subsurface features are likely to be a critical, but often over-looked, factor that influences forest water use and regeneration following density reduction treatments. Using a case study site in the southern Sierra Nevada Mountains of California, we show that whether forest water use increases or decreases following density reduction, as well as the magnitude and rate of recovery of hydrologic changes, depends strongly on plant accessible water storage capacity within the rooting zone and the extent to which the root structures of neighboring trees interact and share water. We find that in some cases density reduction can increase water yield and productivity of remaining trees for the first few years following treatment. However we also show that when soils are shallow and roots systems overlap, counter-intuitive increases in water use and related declines in productivity can occur due to water stress. Results highlight the importance of accounting for site-specific variation, such as soil water storage capacity, in assessing how fuel treatments may interact with ecosystem water use and drought vulnerability, and ultimately downslope impacts on streamflow.